(untitled) (Research, Society and Development, 2021)
The assessment of heart rate variability (HRV) by linear methods in conjunction with Poincaré plots can be useful for evaluating cardiac regulation by the autonomic nervous system and for the diagnosis and prognosis of heart disease in snakes. In this report, we describe an analysis of HRV in conscious adult corn snakes Pantherophis guttatus (P. guttatus). The electrocardiogram (ECG) parameters were determined in adult corn snakes (8 females, 13 males) and used for HRV analysis, and the RR interval was analyzed by linear methods in the time and frequency domains. There was no sex-related difference in heart rate. However, significant differences were seen in the duration of the P, PR, and T waves and QRS complex; there was no difference in the QT interval. The values for the RR interval varied by 15.3% and 18.8% in male and female snakes, respectively, and there was considerable variation in the values for the high and low frequency domains. The changes in the time domain were attributed to regulation by the parasympathetic branch of the autonomic nervous system, in agreement with variations in the high and low frequency domains. The values for standard deviations 1 and 2 in Poincaré plots, as well as the values of the frequency domain, provide useful parameters for future studies of cardiac function in P. guttatus.